Electrolyte Solutions for "Beyond Li-Ion Batteries": Li-S, Li-O2, and Mg Batteries. (1st January 2019) - Sharon, Daniel; Salama, Michael; Attias, Ran; Aurbach, Doron
Abstract : This article describes electrolyte solutions aspects of three battery systems considered as "beyond Li-ion batteries." The common denominator of these systems is the importance of the nature of the electrolyte solutions, which determines their reversibility. Li-S batteries are very close to practical importance, offering the highest energy density among rechargeable batteries. Li-oxygen systems are theoretically most promising, but the poor compatibility of most polar-aprotic solvents with the oxygen reduction species is a major obstacle for practical development. Developing rechargeable Mg batteries also involves a challenge in the choice of electrolyte solutions compatible with both reversible Mg anodes and high potential/high capacity Mg ions insertion cathodes.